(untitled) (Research, Society and Development, 2020)
Chronic Non Communicable Diseases represent the main causes of mortality in the world and are responsible for high morbidity rates and decreased quality of life. Such conditions present as main risk factors those considered modifiable. Thus, it is necessary that health professionals develop intersectoral and interdisciplinary actions in order to reverse the impact of these pathologies. Among these diseases, Systemic Hypertension (SAH) and Diabetes Mellitus (DM) deserve mention. This article aims at characterizing the sociodemographic profile and understanding about the satisfaction of the care of users with diagnosis of systemic arterial hypertension and/or diabetes mellitus (DM) living in three cities of central Rio Grande do Sul. It is a descriptive and exploratory study, of a quantitative nature, prepared within the second edition of the Work for Health Education Program - PET SAÚDE (2012 to 2014). For data collection, the user evaluation on Care for Chronic Conditions and the precepts of the International Classification of Functionality, Disability and Health (ICF) were used. The sample included 898 resident subjects from three municipalities belonging to the 4th Regional Health Coordination-RS. The predominance of women, with incomplete primary education and married was observed. Many users evaluated the care offered by Basic Care services as regular. Therefore, it is relevant to modify the form of health care; one possibility is to involve the subjects in their care process, ensuring co-responsibility and greater resolution of demands.